2017
DOI: 10.1016/j.marenvres.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Determining Good Environmental Status under the Marine Strategy Framework Directive: Case study for descriptor 8 (chemical contaminants)

Abstract: The European Union Marine Strategy Framework Directive (MSFD) requires individual member states to develop a robust set of tools for defining eleven qualitative descriptors of Good Environmental Status (GES), such as demonstrating that "Concentrations of contaminants are at levels not giving rise to pollution effects" (GES descriptor 8). Adopting the recommendations of the ICES/OSPAR Study Group for the Integrated Monitoring of Contaminants and Biological Effects (SGIMC), we present a case study demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The combination of chemical and biological analyses represents an added value for monitoring and management protocols, in line with the recent European Directives which recommend the use of multiple quality indicators for aquatic ecosystems (Lyons et al, 2010(Lyons et al, , 2017Lehtonen et al, 2014). Although multidisciplinary approaches are universally accepted from a conceptual point of view, some critical aspects still limit their practical application in standardized procedures of the risk assessment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The combination of chemical and biological analyses represents an added value for monitoring and management protocols, in line with the recent European Directives which recommend the use of multiple quality indicators for aquatic ecosystems (Lyons et al, 2010(Lyons et al, , 2017Lehtonen et al, 2014). Although multidisciplinary approaches are universally accepted from a conceptual point of view, some critical aspects still limit their practical application in standardized procedures of the risk assessment.…”
Section: Discussionmentioning
confidence: 94%
“…The use of multidisciplinary studies for the characterization of aquatic environment quality is highly encouraged also by European Directives such as the Water Framework Directive (WFD, Directive 2000/60/EC) and the Marine Strategy Framework Directive (MFSD, Directive 2008/56/EC), which require member states to evaluate and classify the ecological status of water bodies through the integration of different quality indicators. Strategies for integrated chemical and biological monitoring have been described and recently adopted by various international agencies or working groups such as OSPAR, HELCOM, MEDPOL, ICES (Broeg and Lehtonen, 2006;HELCOM, 2010;Davies and Vethaak, 2012;OSPAR, 2013;Hylland et al, 2017;Lyons et al, 2017;Vethaak et al, 2017): a recognized advantage of such approaches is the added interpretative value derived from the integration of multiple typologies of studies, thus improving our ability to describe and interpret variations of environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For a site or region to obtain good environmental status (GES) in respect to descriptor 8 of the MSFD, it has been suggested that 95% of the integrated chemical and biological determinants should be below EACs (ICES 2011;Lyons et al 2016). In this way, a failure of reaching GES can be avoided in the case of sites with some outliers.…”
Section: Discussionmentioning
confidence: 99%
“…For each chemical, a ratio-to-criterion (RC) value was calculated as the ratio of measured contaminant concentration and corresponding assessment criterion to yield RCs_ BAC , RCs_ EAC or RCs_ EQS , and RCs_ MPC . The RC values were then used to compute chemical pollution indexes (CPIs) as well as to assess the status of each matrix and site through the application of a traffic light system (Lyons et al 2016). To obtain CPI (which is a numerical value that gives a single assessment of contamination for each matrix at each site), the RCs were aggregated using the formula of CPI = ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi RC 1 ÂRC 2 … Â RC n n p (Tomlinson et al 1980), where n is the total number of contaminants included in the calculation.…”
Section: Assessment Approachmentioning
confidence: 99%
“…European flounder (Platichthys flesus) have been used internationally to monitor the effects of exposure to marine pollution since the 1980s (Malins et al, 1985;Vethaak and Reinallt, 1992;Stentiford et al, 2003;Lyons et al, 2015). Such lesions have been associated with exposure to anthropogenic contaminants such as polycyclic aromatic hydrocarbons (PAHs) (Malins et al, 1985;Vethaak and Reinallt, 1992).…”
Section: Introductionmentioning
confidence: 99%